2014
DOI: 10.1192/apt.20.2.82
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of treatment guidelines for specialist mental health care

Abstract: A huge gap exists between the production of evidence and its take-up in clinical practice settings. To fill this gap, treatment guidelines, based on explicit assessments of the evidence base, are commonly employed in several fields of medicine, including schizophrenia and related psychotic disorders. It remains unclear, however, whether treatment guidelines have any impact on provider performance and patient outcomes, and how implementation should be conducted to maximise benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A Cochrane review recently investigated whether there was evidence that schizophrenia guidelines had any impact on provider performance or patient outcomes [5]. Only five studies were found and due to methodological heterogeneity, a meta-analysis was only possible for the question for antipsychotic drug therapy.…”
Section: Guideline Development and Implementationmentioning
confidence: 99%
See 1 more Smart Citation
“…A Cochrane review recently investigated whether there was evidence that schizophrenia guidelines had any impact on provider performance or patient outcomes [5]. Only five studies were found and due to methodological heterogeneity, a meta-analysis was only possible for the question for antipsychotic drug therapy.…”
Section: Guideline Development and Implementationmentioning
confidence: 99%
“…The European Psychiatric Association considers (Grade of recommendation: A) that quality assurance in mental healthcare can be fostered by using established national guidelines and quality indicators for the diagnosis and treatment of specific mental disorders (meso-level; Section 3.5; evidence level I; [5,33,95,109]). …”
Section: Recommendation 10mentioning
confidence: 99%